Power gearbox and pitch control mechanism for open rotors - investigation of preliminary design methodologies - San Benito Pastor, Diana Guiomar (Cranfield University, 2018)
Poster presented at the Cranfield Doctoral Network Annual Event, September 2018.The expected result of this PhD research is a design methodology that would allow establishing the feasibility of a pusher counter-rotating open rotor (CROR) engine architecture, taking into account both performance and mechanical integrity aspects. The analysis will consider the preliminary design of the main technology enablers, i.e. the advanced power gearbox (PGB) and the pitch change mechanism (PCM), delving into sizing, mechanical integrity aspects and optimal positioning of the components within the propulsion system. The study will then be extended to assess: Design for performance through simulated flight trajectory assessments over selected missions; Lifing aspects of the components and their implication on maintenance costs; Economic benefits through a financial viability analysis. A key requirement is to optimize these objectives by determining the minimum size of the power transmission system of the CROR engine to transmit power from the free turbine to the counter-rotating propellers. This requirement will need to be met without compromising its mechanical integrity nor the overall performance of the engine.
Keywords: gearbox; aircraft; power transmission systems; CranfieldDN2018; Aerospace Engineering